2023
DOI: 10.3390/en16124787
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Digital Twin for Increasing Efficiency of Renewable Energy Sources

Abstract: This paper presents an analysis of the instability of the electricity generation of renewable energy sources (RESs), specifically Digital Twins of RESs. The first part deals with the analysis of RES electricity generation around the world and Ukraine. The following chapter describes features of functioning power grids in modern conditions in Ukraine and ways to ensure the balance reliability in the power system for conditions of high-grade RES integration. The rapid increase in electricity generation RESs caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…7. Main factors, which influence on the power generations PV system, are irradiation, wind speed and temperature [27] for Ukraine conditions. Presented on Fig.…”
Section: Criterion Programming (сP) As An Optimization Methods and As...mentioning
confidence: 99%
“…7. Main factors, which influence on the power generations PV system, are irradiation, wind speed and temperature [27] for Ukraine conditions. Presented on Fig.…”
Section: Criterion Programming (сP) As An Optimization Methods and As...mentioning
confidence: 99%
“…Simulations have shown that a suitable combination of AC coupling and DC coupling systems in one community can mean energy savings in the order of units of percent and even make the resulting consumption diagram more efficient. The following text will clarify the different behavior of both variants of the hybrid system under relevant conditions [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies [69][70][71], the processes of application of digital twins in the realization of energy systems, which ensures the efficiency of functioning of the used energy systems and increase their flexibility, due to the realization of dispatching systems, are considered. So, in [72], the process of creation and implementation of a digital twin for the energy system for which the procedures of long-term and short-term forecasting, planning, maintenance and operational control in real time were realized. The use of such a system is aimed at improving the quality of the distributed generation parameter management, which is especially relevant when RES are involved, the generation of which can undergo strong changes.…”
mentioning
confidence: 99%